Linking the influence of diagenetic properties and clay texture on reservoir quality in sandstones from NW Borneo. (October 2020) - Usman, Muhammad; Siddiqui, Numair A.; Mathew, Manoj; Zhang, Shiqi; El-Ghali, Mohamed A.K.; Ramkumar, Mu; Jamil, Muhammad; Zhang, Yaxuan
Abstract: Reservoir studies in the Sandakan sub-basin NW Borneo are challenging and inexplicable due to complex diagenetic effects such as compaction, cementation, dissolution and depositional means including grain size, sorting and packing with reference to clay texture. These diagenetic effects together impart significant amounts of uncertainty on reservoir quality assessment. In this regard, we documented the mineralogical, diagenetic and reservoir properties of sandstones from the Sandakan Formation, NW Borneo through thin sections, SEM, XRD, XRF, He-porosimeter and poroperm. In order to analyze the influential parameters, we used matrix, grain rearrangement and clay coating around detrital grains for the reservoir quality. Our results show that the sub-litharenites to quartz arenite that dominate in the sandstones are drawn from recycled orogenic sand. Furthermore, reservoir properties of the sandstones were ascertained to be controlled by diagenesis, micro quartz with clay coatings and pressure dissolution of feldspar with the alteration of lithic fragments. The result shows that the physical compaction, rearrangements and ductility of grains were the reasons that reduced porosity and permeability. The main reason for porosity reduction in the present study is pressure dissolution that resulted in the form of chemical compaction induced by micas with grain contacts. Nonetheless, through SEM and petrography, clay coatings around the grains and dissolution of feldspar were found to optimally contribute to the preservation of reservoir properties. Dissolution of feldspar and kaolinization resulted in the formation of secondary porosity that allows meteoric water to percolate through the open and detachment spaces of quartz or other grains. This percolation is also responsible in enhancing the pore throat radii in the reservoir media of the analyzed sandstones. These traits are obliging to diagenetic effects on porosity and permeability, which are linked with the physical compaction and clays coating to reduce and preserve the reservoir properties respectively of same type of reservoirs globally. Highlights: Diagenetic events and depositional means controlled the reservoir quality of NW Borneo Siliciclastic Deposits. Physical compaction and clays coating are the sources to reduce and preserve the reservoir properties. Diagenetic reasons and influential parameters for the reduction and preservation of porosity and permeability.